Budget preparation : Keterlibatan Karyawan dalam Proses Anggaran dan Implikasinya terhadap Efektivitas Anggaran Organisasi Publik - Dea Fitria Maslaha; Al Amanda Chorra Nabela; Anna Marina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of employee involvement in the budgeting process on budget effectiveness in public organizations. A quantitative approach was employed through a survey conducted among employees of Regional Government Organizations (Organisasi Perangkat Daerah/OPD) in Surabaya. Data were collected using questionnaires distributed to respondents directly involved in the budgeting process. The data were analyzed using multiple linear regression to examine the relationship between employee participation and budget effectiveness. The results indicate that employee involvement in the budgeting process has a positive and significant effect on the effectiveness of public sector budgeting. Such involvement enhances the understanding of budgetary goals, strengthens implementation commitment, and minimizes potential discrepancies in budget management. These findings reinforce the importance of participatory approaches in budget governance to improve accountability and organizational performance in the public sector.